Evaluasi Pelaksanaan Peraturan Daerah Kota Padang Nomor 21 Tahun 2012 tentang Pengelolaan Sampah (Studi Kasus Pemilahan Sampah di Kecamatan Padang Selatan) - Riska, Mutiara; Mubarak, Adil (Lembaga Yasin AlSys, 2025)
This study is motivated by the suboptimal dissemination and implementation of waste sorting practices, the lack of supporting facilities, and the low awareness and participation of the community in sorting waste at its source. The objective of this research is to evaluate the implementation of Padang City Regional Regulation No. 21 of 2012 on Waste Management, specifically focusing on the waste sorting aspect in South Padang District. A qualitative approach with a descriptive method was employed. Informants were selected through purposive sampling, and data were collected through observation, interviews, and document analysis. Data validity was tested using triangulation, while data analysis was conducted through reduction, presentation, and conclusion drawing. The findings indicate that, in terms of input, the availability of resources, budget, and waste sorting facilities remains insufficient to reach all community levels. In the process dimension, socialization and training activities are irregular and not sustained. At the output level, the available facilities and programs have not been optimally utilized. Meanwhile, the expected outcome namely, behavioral changes in community waste sorting at the source has not been significantly achieved. The study concludes that the implementation of the waste sorting policy in South Padang District has not been effective. The implication is that more sustainable planning, adequate resource allocation, and strategies to enhance community participation are needed to achieve the objectives of a source-based waste management policy.